PENGARUH PENGGUNAAN MEDIA DOMINO CARD PENGALAMANKU TERHADAP HASIL BELAJAR SISWA KELAS II UPT SDN 203 GRESIK - Saroh, Emi Mai; Nafiah, Nafiah; Hidayat, Muhammad Thamrin; Rulyansa, Afib (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The problem in this study is that the teaching process is still teacher-centered which results in the teacher being more active than the students so that during the learning process students get bored easily which affects their learning outcomes so they use domino card learning media from my experience. The purpose of this research is to determine the effect of using domino card media my experience with the learning outcomes of class II students at UPT SD Negeri 203 Gresik which is known from the difference in the average pretest and posttest that has been done. Data collection techniques in the form of questions pretest and posttest. This research uses a type of quantitative research with Pre-Experimental Design. Because it's not a real experiment yet. Data analysis used parametric analysis test with paired t-test analysis (2 tailed). The results of this study indicate that there are differences in student learning outcomes before and after the implementation of the domino card media, my experience with an average increase of 70.65 compared to before using the domino card media, my experience was an average of 68.71. the results of the output test statistic test paired T-Test (2 tailed) which shows sig (2.tailed) 0.000 <0.05. This shows that my experience domino card learning media can effectively improve student learning outcomes, because student responses are very positive with the use of my experience domino card media.